BIBLIOMETRIC SURVEY OF 5G IN INDIA - et. al., Kiran Semwal (International Journal of Modern Agriculture, 2021)
The telecommunications industry is in strong competition with all service providers and is trying to reach the top by using attractive plans and evolving its network standards to attract and retain its customers. One of subsector of telecommunication industry i.e. 5G is anticipated to deliver data speeds hence enhances the overall customer experience and drastically improves efficiency in IoT devices. This paper gives a comprehensive bibliometric survey of the literature of usage of 5G in India. We have used the Scopus database for searching and analysing the research papers and VOSviewer visualization tool for obtaining the link strength between authors, organizations, countries, and keywords. The survey covers 99 articles. With the emerging technologies 5G has become significant from the year 2006. Based on the analysis there is rise in the publication since last 5 years. The study also investigates top affiliated universities as well as major funding sponsors. Using co-authorship analysis, we have created a map that shows the link strength between authors. Also, using a bibliographic coupling, we mapped the collaborative networks at a country level.